A STUDY ON STUDENTS’ MOTIVATION TOWARDS LEARNING ENGLISH LANGUAGE: A CASE STUDY OF ONE SENIOR HIGH SCHOOL IN PEKANBARU - Yuzulia, Irza (English Community Journal, 2021)
Motivation is the main point to determine the students’ desire to learn English. Students’ motivation will be correlated with their performance and achievement during the learning process. The research aimed to find out students’ motivations in learning English and the kinds of motivations they have. The respondents of this study were sixty two third-grader students of senior high school in Pekanbaru. This study used quantitative and descriptive method where the information delivered based on the actual condition. A questionnaire that consists of twenty-five questions and open-enede questions was delivered to the students. The answers of the respondents were analyzed and computed to find out the mean valaue of each kind of motivation. Based on the result of the study, it is found that the students have high motivation to learn English. They want to be able to communicate fluently, to understand reading materials and to get better job in the future. However, the students do not neglect the aim of learning English at school is to pass the examination. The teachers are suggested to encourage students to focus on their improvement, not only grade or examination.